Case Report: Five Adult Cases of H3K27-Altered Diffuse Midline Glioma in the Spinal Cord - Gu, Quanquan; Huang, Yajing; Zhang, Hao; Jiang, Biao (Frontiers in Oncology, 2021)
Background: Diffuse midline glioma with H3K27-altered (DMG-H3K27a) is a novel tumor entity of the pediatric-type diffuse high-grade tumor in the most recent WHO CNS 5. It mostly affects children and is only rarely found in adults. The tumor has a high level of aggressiveness, rapid progression and a bad prognosis. The spinal cord is the most common site of DMG-H3K27a in adults. Rare adult cases of primary DMG-H3K27a in the spinal cord were reported in this study, together with clinico-histopathologico-radiographic data. Methods: From January 2016 to December 2020, we conducted a retrospective study of 5 adults with primary DMG-H3K27a, analyzing their clinical, pathohistological, and radiographic datasets from first diagnosis to follow-ups. Results: All the 5 patients were diagnosed for the first time and were given full treatment. In three of the five patients, post-operative follow-up revealed tumor recurrence. The longest survival of the 5 patients was 45 months at the time of report submission, while the longest progression-free survival (PFS) following surgery was 20 months. Immunohistochemical studies showed the tumors were featured by aggressive behavior (grade 4) and positive for the H3K27M mutation. The radiographic appearances were varied, but they were all initially mistaken as benign. DMG-H3K27a in the spinal cord was characterized by isointense/hyperintense on T1WI and isointense/hyperintense on T2WI, as well as cystic necrosis and peripheral spinal cord edema, as well as central canal enlargement and other types of enhancement. Conclusion： This is the first case report to focus on adult DMG-H3K27a of the pediatric-type diffuses high-grade gliomas in the spinal cord. On our cases, we discovered the following: 1) adults had a better prognosis with a longer PFS than prior pediatric reports; 2) despite aggressive behavior under the microscope, radiographic appearances of the tumors were less aggressive; and 3) adjuvant treatment, including TCM, may have had a role in the prognosis.